Kank proteins: A new family of ankyrin-repeat domain-containing proteins - Zhu, Yun; Kakinuma, Naoto; Wang, Yong; Kiyama, Ryoiti (Biochimica et biophysica acta, 2008)
The human Kank gene was found as a candidate tumor suppressor for renal cell carcinoma, and encodes an ankyrin-repeat domain-containing protein, Kank. Here, we report a new family of proteins consisting of three Kank (Kank1)-associated members, Kank2, Kank3 and Kank4, which were found by domain and phylogenetic analyses. Besides the conserved ankyrin-repeat and coiled-coil domains, there was a conserved motif at the N-terminal (KN motif) containing potential motifs for nuclear localization and export signals. Gene expression of these genes was examined by RT-PCR at the mRNA level and by Western blotting and immunostaining at the protein level. Kank family genes showed variations in the expression level among tissues and kidney cell lines. Furthermore, the results of overexpression of these genes in NIH3T3 cells suggest that all of these family proteins have an identical role in the formation of actin stress fibers.